A organização político-sindical das e dos assistentes sociais no contexto do novo sindicalismo no estado do Paraná (1983 - 1994) - Martins, Tatiane (2022)
The object of study of this work has as its theme the political organization of social workers, in the particularity of the new unionism in the State of Paraná. The delimitation of the problem asks: in the context of the new Brazilian unionism, what factors influenced the decision-making for the creation and subsequent suspension of the activities of the Union of Social Workers in the State of Paraná in the 1983s and 1994s? In order to answer the question, the general objective was defined: to analyze the influence of the political-union organization of social workers in the context of the new unionism that influenced the creation and suspension of the activities of the Union of Social Workers in the State of Paraná. Based on the theoretical-methodological basis of the Marxian analysis and the Marxist tradition, the study was based on bibliographic research in the productions of authors who discuss the theme, as well as on documentary and field research with semi-structured interviews with protagonists who experienced this process. For data analysis, content analysis was used as a procedure. The analysis had as a reference the understanding that social workers are members of the working class and that the decision-making of the political-union organization by branch of activity was a strategy to strengthen the class. At the same time, it is considered that the creation of the union of the category and subsequent suspension of union activities in that period needs to be the subject of more studies and deepening. The growing precariousness and flexibility of working conditions and relations to the detriment of the interests of capital are daily challenges for social workers as part of the working class. It is understood that the collective perspective of incorporation of professional categories in the union spaces of general struggle of the working class, presented and defended by CUT (1986), remained unfinished, not being supported in its socio-historical unfolding in Brazil, as well as by the category professional in the State of Paraná.